Analysis and conservation of social attributes in traditional shopping districts towards revatilisation of town centres in recession: Balikesir as a case study. (29th November 2010) - Cetin, Murat
In this study, it is of interest to reveal the relationships between morphological aspects of traditional town centre and their social attributes of civic life. The history of communal life and human settlements has always been associated with the history of shopping. Traditional shopping districts have been vibrant public realms. Nevertheless, social harmony and unity observed in traditional societies have been fragmented by global socio-economic changes. Consequently, today's shopping places are dislocated towards the outskirts of traditional town. Hence, old town centres are neglected causing them to lose their value as traditional spaces enhancing public interactions. Therefore, morphological characteristics that maintain the unity between shopping activity and social fabric in traditional shopping space should urgently be clarified. Along this purpose, morphological characteristics required for revitalising traditional shopping spaces of Balikesir are analysed. Consequently, it is aimed to develop a new methodological basis for formulating cultural, spatial transformation of shopping spaces.